Determinan Faktor yang Berhubungan dengan Quality of Nursing Work Life (QNWL) Perawat Perempuan (Journal of Telenursing (JOTING), 2025)
This study aims to explore factors related to the Quality of Nursing Work Life (QNWL) in female nurses. QNWL is an important indicator that reflects the welfare of nurses and the overall quality of nursing services. The method used is a quantitative approach with a cross-sectional design. Data were collected through questionnaires from 75 female nurses, with variables including individual characteristics (marital status, child status, and education level), work stress level, and QNWL. The results showed that there was a significant relationship between marital status (p-value 0.048), child status (p-value 0.01), and work stress (p-value 0.027) with QNWL. However, there was no relationship between education level (p-value 0.95) and QNWL. In conclusion, several individual factors and work stress levels influence QNWL in female nurses. These findings can be used to formulate hospital policies to create a more conducive work environment that improves nurse welfare and the quality of nursing services. Keywords: Nursing Services, Female Nurses, Work Stress, Quality Of Nursing Work Life